2017
DOI: 10.5588/ijtld.16.0845
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in migrants in low-incidence countries: epidemiology and intervention entry points

Abstract: As tuberculosis (TB) rates continue to decline in native populations in most low TB incidence countries, the proportion of TB patients born outside their country of residence ('foreign-born') increases. Some low-incidence countries have experienced a substantial increase in TB rates related to recent increases in the number of asylum seekers and other migrants from TB-endemic countries. However, average TB rates among the foreign-born in low-incidence countries declined moderately in 2009-2015. TB in foreign-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
131
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 0 publications
0
131
0
2
Order By: Relevance
“…This is a representative case of tuberculosis (TB) diagnosed in a low TB incidence country during a time period of intensified migration flow from Africa to Europe. In recent years, TB in migrants has represented a major public health challenge for low TB incidence countries such as Italy (Lönnroth et al, 2017;Sotgiu et al, 2017a). Incidence rates in foreign-born populations coming from high TB burden areas (e.g., Somalia) are higher than those recorded in the native European population; furthermore, migrants show a higher probability of developing the disease from latent TB infection acquired in the country of origin or on the route to Europe (Sotgiu et al, 2017a;Walker et al, 2018).…”
mentioning
confidence: 99%
“…This is a representative case of tuberculosis (TB) diagnosed in a low TB incidence country during a time period of intensified migration flow from Africa to Europe. In recent years, TB in migrants has represented a major public health challenge for low TB incidence countries such as Italy (Lönnroth et al, 2017;Sotgiu et al, 2017a). Incidence rates in foreign-born populations coming from high TB burden areas (e.g., Somalia) are higher than those recorded in the native European population; furthermore, migrants show a higher probability of developing the disease from latent TB infection acquired in the country of origin or on the route to Europe (Sotgiu et al, 2017a;Walker et al, 2018).…”
mentioning
confidence: 99%
“…Symptoms of the active phase of tuberculosis, such as coughing and fatigue, may go unnoticed to already infected individuals and health care workers in crisis settings, because they are insidious (17). Dangerous situations encountered during migration, including overcrowding, incarceration, malnutrition, challenges to access health care, low adherence to treatment, associated risk of HIV infection and exposure to other migrants from higher incidence countries also contribute to the risk of contamination by M. tuberculosis and progression to disease (8,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…The higher TB incidence in foreign-born persons living in low-incidence countries is associated with the high TB incidence in their country of origin, more often following reactivation of a latent TB infection owing to poor living conditions in the host country. Moreover, the increased risk of Mycobacterium tuberculosis infection can be associated with travels to the native country, involving new generations of foreign-born families [5]. Cowger and colleagues showed that having at least one parent born outside of the USA increased the likelihood of developing TB by 3.5 times, while having two parents born outside of the USA increased the risk up to 8.5 times [4].…”
Section: Introductionmentioning
confidence: 99%